1999
DOI: 10.1046/j.1462-5822.1999.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of alpha5beta1 integrins in interleukin 8 production induced by oral viridans streptococcal protein I/IIf in cultured endothelial cells

Abstract: SummaryUsing human endothelial cells, we de®ne a mechanism that accounts for the induction of interleukin 8 (IL-8) by protein I/IIf, an adhesin from Streptococcus mutans serotype f. We report that protein I/IIf interactions with endothelial cells increased the tyrosine phosphorylation of three cellular components with relative mass of 145 000, 125 000 and 70 000 in endothelial cells. These proteins were identi®ed as phospholipase Cg (PLCg), focal adhesion kinase (FAK) and paxillin after immunoprecipitation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…We showed previously that protein I/II, a ligand of integrin ␣ 5 ␤ 1 , induces cytokine production by human endothelial and epithelial cells and FLSs and that this effect is FAK dependent (5,6). In this study, we first verified the capacity of protein I/II to stimulate phosphorylation of FAK in murine bone marrow-derived macrophages.…”
Section: Protein I/ii a Ligand Of Integrin ␣ 5 ␤ 1 Induces Fak Phomentioning
confidence: 59%
See 2 more Smart Citations
“…We showed previously that protein I/II, a ligand of integrin ␣ 5 ␤ 1 , induces cytokine production by human endothelial and epithelial cells and FLSs and that this effect is FAK dependent (5,6). In this study, we first verified the capacity of protein I/II to stimulate phosphorylation of FAK in murine bone marrow-derived macrophages.…”
Section: Protein I/ii a Ligand Of Integrin ␣ 5 ␤ 1 Induces Fak Phomentioning
confidence: 59%
“…B acterial recognition implicates a wide variety of pattern recognition receptors specific for pathogen-associated microbial patterns (PAMPs), 5 including TLRs, lectins, scavenger receptors, and integrins. Among them, TLRs are critical for the development of innate immune responses (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FLS express various integrins, and in this study, we also explored the ultimate implication of ␣5␤1 integrin, a well-known receptor of several bacterial PAMPs, in BAFF synthesis (26)(27)(28). Protein I/II, an adhesin derived from viridans streptococci, is an established ␣5␤1 integrin ligand that induces the release of classic proinflammatory cytokines, such as IL-6 and IL-8, by FLS (18). An important result in this study was the finding that protein I/II induced BAFF transcription and secretion by activated FLS.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of PRRs, such as Toll-like receptor 2 (TLR-2), TLR-4, and TLR-9, as well as numerous integrins are expressed by FLS, and their expression is increased in response to inflammatory stimuli (16,17). We previously showed that LPS, bacterial lipopeptide (BLP), and protein I/II, which are ligands of TLR-4, TLR-2, and ␣5␤1 integrin, respectively, can trigger the release of IL-6 and IL-8 from activated FLS (18,19).…”
mentioning
confidence: 99%